2017
DOI: 10.1111/1742-6723.12744
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of alternative therapies among paediatric emergency department patients

Abstract: AT use is common among paediatric ED patients. Parents who arrange AT have differing perceptions of AT usefulness and safety from those who do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(86 reference statements)
4
4
0
Order By: Relevance
“…The prevalence of Rongoā use is similar to a study carried out among NZ adults that also reported use at 7%, and although a higher proportion of users were of Māori heritage (83%), Rongoā only accounted for 11% of CAM use among Māori in the study [24]. The prevalence of CAM use among indigenous pediatric populations is infrequently reported, even when ethnicity data were collected [2,4,5,9]. In systematic reviews of indigenous adult populations, CAM use has been reported at 15-68% for those with diabetes [25], and 18-58% of those with cancer, with 58% prevalence among Māori [26].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The prevalence of Rongoā use is similar to a study carried out among NZ adults that also reported use at 7%, and although a higher proportion of users were of Māori heritage (83%), Rongoā only accounted for 11% of CAM use among Māori in the study [24]. The prevalence of CAM use among indigenous pediatric populations is infrequently reported, even when ethnicity data were collected [2,4,5,9]. In systematic reviews of indigenous adult populations, CAM use has been reported at 15-68% for those with diabetes [25], and 18-58% of those with cancer, with 58% prevalence among Māori [26].…”
Section: Discussionsupporting
confidence: 76%
“…CAM are commonly used to support, or to replace, conventional allopathic treatments as well as to improve overall well-being [1,2]. The use of CAM is generally high among children [3], especially those with chronic health conditions who may utilize multiple CAM therapies [4,5]. Studies among general pediatric populations are less frequently reported, and little is known about CAM use for children with or without health conditions in New Zealand (NZ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common were massage (16%), chiropractic therapy (9.8%), relaxation (7.2%), meditation (6.2%), aromatherapy (6.1%), and spiritual healing (4.3%). 5 In our country, parents commonly use CAM including prayer for their children's health. Top et al 6 reported that 97.7% of parents of ill children had used at least one CAM method for mostly respiratory complaints, and 17.5% mothers used prayer.…”
mentioning
confidence: 99%
“…Eleven AEs could not be rated for severity due to insufficient information ( Table 2 ) [ 30 , 32 , 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%